Severe Leukemoid Reaction in a Case of Soft Tissue Sarcoma: A Case Report. Issue 4 (October 2019) - Xing, Zhiqing; Scott, Brandon
Abstract : Case: A 62-year-old woman presented with severe leukocytosis and systemic symptoms including fatigue, low appetite, and weight loss. After 4 months of evaluation by doctors with extensive laboratory tests and imaging studies, a soft tissue sarcoma in the left posterior distal thigh was revealed. Quickly after surgical excision of the soft tissue sarcoma, the leukocytosis and systemic symptoms were dramatically resolved. Conclusions: Leukemoid reaction can present as a paraneoplastic syndrome. Awareness of soft tissue sarcoma as a possible cause of leukemoid reaction may help improve the early diagnosis and subsequent early intervention in future cases.